Lumbar Vertebral Endplate Defects on Magnetic Resonance Images: Classification, Distribution Patterns, and Associations with Modic Changes and Disc Degeneration - Feng, Zhiyun; Liu, Yuanhao; Yang, Ge; Battié, Michele C; Wang, Yue (Spine (Philadelphia, Pa. 1976), 2018)
A cross-sectional magnetic resonance (MR) imaging study. To classify and characterize endplate defects using routine lumbar MR images and to determine associations of endplate defects with Modic changes (MCs) and disc degeneration. Previously, a cadaveric study revealed that endplate lesions were common and associated with back pain history. New in vivo approaches appropriate for clinical studies are needed to further this potentially important line of research on the clinical significance of endplate lesions, including their relation with MCs, disc degeneration, and back pain. Using a MRI archive, 1564 endplates of 133 subjects (59 men and 74 women, mean age 58.9 ± 11.9 years) with the presence of MCs were retrospectively collected from April of 2014 to June of 2015. On the basis of morphological characteristics, a protocol was proposed to identify three distinct types of endplate defects, including focal, corner, and erosive defects. The location, size, and distribution patterns of various endplate lesions were characterized. MCs and disc degeneration were measured to examine their associations with endplate defects. Endplate defects were observed in 27.8% of endplates studied. Greater age was associated with the presence of endplate defects. Focal defects were the most common (13.5%), followed by erosive defects (11.1%) and corner defects (3.2%). Defect types also differed in size and distribution patterns. Endplate defects and MCs had similar distribution patterns in the lumbar spine. The presence of endplate defects were associated with the presence of MCs (odds ratio = 4.29, P < 0.001), and associated with less disc signal intensity and disc height, and greater disc bulging (P < 0.05). The three endplate defects identified on routine MR images appear to represent different pathologies and may play a key role in the pathogenesis of MCs. This classification system may facilitate clinical studies on endplate defects. 4.